Exchange rate volatility and international trade: International evidence from the MINT countries - Asteriou, Dimitrios; Masatci, Kaan; Pilbeam, Keith (ELSEVIER, 2016)
This paper examines the effect of exchange rate volatility on international trade volumes for Mexico, Indonesia, Nigeria, and Turkey. We use volatility predicted from GARCH models for both nominal and real effective exchange rate data. To detect the long-term relationship we use the autoregressive distributed lag (ARDL) bound testing approach, while for the short-term effects, Granger causality models are employed. The results show that, in the long term, there is no linkage between exchange rate volatility and international trade activities except for Turkey, and even in this case, the magnitude of the effect of volatility is quite small. In the short term, however, a significant causal relationship from volatility to import/export demand is detected for Indonesia and Mexico. In the case of Nigeria, unidirectional causality from export demand to volatility is found, while for Turkey, no causality between volatility and import/export demand is detected. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Exchange rates; International trade; Volatility; Causality; IMPACT; COINTEGRATION; EXPORTS; GROWTH; Business & Economics